Debt to Equity Ratio, Current Ratio, and Return on Investment on Stock Prices in Conventional Commercial Bank Listed on The Indonesian Stock Exchange - Maryam, Siti; Gemina, Dwi; Samsuri, Samsuri; Asmi, Erni Amriani; Gunawan, Rachmat (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
To anticipate fluctuations in share value, investors rely on empirical research. Ratios are often used in financial statement studies. The focus of the research is on traditional commercial banks listed on the Indonesian Stock Exchange so that stock exchange trading trends can be identified. Debt-to-equity ratio, current ratio, return on investment, and bank stock price are just some of the financial metrics we'll look at. The 45 participating banks are listed on the Indonesia Stock Exchange and are part of this research. Thirteen or eleven banks were randomly selected for this investigation. Share prices can also be influenced by other indicators such as return on investment (ROI), current ratio, and debt-to-equity ratio. The value of a company is negatively influenced only by the Current Ratio. The Current Ratio is considered to have a detrimental influence because capital market investors do not consider the extent of this financial measure when formulating investment choices.